Moreau de Saint-Méry and the Apology of racial discrimination - (:unkn) unknown (My University, 2023)
An important aspect of our doctoral research consists in the fact of noting that history has been carved essentially on the model of Western man whose civilization wants to be globalizing, gradually seeking to pack the other societies estimated to be behind the "great and true history", that is to say, the history of the Western world, the one that Matthieu Renault (2018) would call "the official-white history" which would have been erected in a kind of glorification of the people white, and in which the contribution of blacks had hitherto been systematically concealed, distorted, discriminated against, trivialized, etc. This vision of the Western world is noticed by many philosophers and historians, for whom this European schema would be, according to Laënnec Hurbon (2007), the prototype, worthy of being imitated by other societies. And the analysis, for example, of the Description topographique…(1797), historical work of Moreau de Saint-Méry, would allow us to understand these disavowals with regard to the potential of the interior values ​​of the Negro slaves, born or come from Africa. We notice, in fact, in the work of this historian, a rather pejorative description of the portrait of the black African, for reasons, moreover, very unsound. The Black, in his eyes, is not sufficiently similar to the White, the latter being, for him, made of an imposing body which charms and touches the senses, and of an admirable beauty which satisfies the pleasure of the eyes. Le Blanc's body is, therefore, arranged with a harmony well observed by Moreau de Saint-Méry between certain parts of the body, and between the features of the face: "elongated nose, […] hair less frizzy and more likely to extend and to be braided than the kind of wool which generally covers the head of the African, [...] less thick lips and more regular features than the African Negroes", affirms, Moreau Saint-Méry (1797: 26-55 ). The problem with these kinds of affirmations is th
Keywords: African Research